Gerakan Literasi Desa: Membaca Untuk Masa Depan - Adi Robih Setiana (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Literacy is a crucial foundation in building an empowered and sustainable society. The ability to read, write, and comprehend information serves not only as a basic skill but also as a key to improving the quality of human resources, economic empowerment, and social and political participation. The reality in Village X shows that the community's literacy rate is still low, indicated by limited reading facilities, low interest in reading, and a lack of mentoring from literacy workers. This condition motivated the implementation of a community service program titled "Village Literacy Movement: Reading for the Future." The community service method was conducted through a participatory approach by actively involving the community in every stage, from preparation, implementation, mentoring, to evaluation. The main activities included the establishment of a Community Reading Center (TBM), a family reading program, literacy volunteer training, digital literacy integration, and the organization of a Village Literacy Festival. The results of the activity showed an increase in reading interest among children and parents, the formation of village literacy volunteers, and the creation of local works in the form of folklore and poetry. In addition, the community began to recognize digital literacy as a means to expand access to knowledge. The discussion emphasizes that literacy is not merely an academic activity, but a social movement that strengthens community bonds and opens up opportunities for village development. The challenges still faced are the limited collection of reading materials, uneven internet access, and the sustainability of the program post-community service. Therefore, continuous support from the village government, schools, and the community is needed to maintain the literacy ecosystem. In conclusion, the "Village Literacy Movement: Reading for the Future" in Village X successfully increased community literacy awareness and practices. This program has the potential to become a literacy-based village empowerment model that can be replicated in other regions, so that literacy truly becomes a long-term investment for the nation's future.